Slogans and Posters on Instagram for 2024 Legislative Candidates as Junior High Indonesian Language Learning Media: A Teun Van Dijk's Microstructure Study - Wardana, Muhammad Aditya Wisnu; Rakhmawati, Ani; Suhita, Raheni (Jurnal Lingua Idea, 2024)
This study aims to analyze the critical discourse analysis of microstructure aspects contained in the slogans and Instagram posters of legislative candidates in 2024. The data source of this research is based on Hapri Sianturi's Instagram social media for legislative candidates in 2024 (https://www.instagram.com/haprisianturi/) by observing the linguistic aspects of Instagram posts and the language of Instagram captions. This research uses the critical discourse analysis framework of Teun van Dijk's model to explore the microstructure in the slogans and Instagram posts of legislative candidates in 2024. The research used a qualitative approach and listening method with listening and recording techniques for the data collection. Then, interviews and field observations were conducted at SMP Negeri 1 Surakarta and SMP Negeri 4 Surakarta to determine the relevance of teaching media. The results of research and discussion show that the microstructure aspects of the 2024 legislative candidate Hapri Sianturi are complete. Critical discourse analysis research on posters and slogans of legislative candidates is relevant to learning at the 8th-grade junior high school level using the independent curriculum on the material of Advertising Texts, Slogans, and Posters.